Edukasi Pengenalan Obat Kepada Siswa Sekolah Dasar - Ani Kristiyani; Sarah Puspita Admaja (J.Abdimas: Community Health, 2021)
The problem of rational drug use in the community, especially among students, is still minimal. The government by gema cermat or smart community movement to use drugs which in the context of society expects an in knowledge increase, understanding and skills in using drug properly and wisely so that can lead awareness of drugs using in the community. Health education is an effort that is given guidance to someone or students. Presenting counseling is expected to increase knowledge about proper drugs used for students. The method used in educating students is through material presentation, discussion, quizzes, and playing games. Students are given a pre-test and post-test before and after education. Education to increase students' knowledge is shown from the post-test results obtained that have a higher knowledge value than the pre-test.